2013
DOI: 10.1097/sga.0000000000000005
|View full text |Cite
|
Sign up to set email alerts
|

Exercise in Individuals With Inflammatory Bowel Disease

Abstract: There is increasing evidence that exercise may improve symptoms in individuals with inflammatory bowel disease (IBD). This study aims to explore issues that clinicians may need to consider when giving advice on exercise to such individuals. Limited existing evidence suggests that low to moderate physical activity may improve symptoms without any adverse effects in individuals with IBD. This is largely supported by the findings of the current case series of "exercising" individuals with IBD who reported that lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 31 publications
1
36
0
1
Order By: Relevance
“…Treating fatigue with exercise may sound contradictory, at least to patients, however, in a small case series, patients who reported low-to moderate-intensity exercise (most commonly walking) had a positive effect on their mood, fatigue, weight maintenance, and osteoporosis [91]. Exercise has numerous benefits and this simple recommendation to our IBD patients can have a profound impact on the improvement of their fatigue as well as other aspects of their health.…”
Section: Fatiguementioning
confidence: 86%
“…Treating fatigue with exercise may sound contradictory, at least to patients, however, in a small case series, patients who reported low-to moderate-intensity exercise (most commonly walking) had a positive effect on their mood, fatigue, weight maintenance, and osteoporosis [91]. Exercise has numerous benefits and this simple recommendation to our IBD patients can have a profound impact on the improvement of their fatigue as well as other aspects of their health.…”
Section: Fatiguementioning
confidence: 86%
“…11 human studies [9,15,19,21,23,30,31,34,41,47,48] have looked at the influence of moderate exercise programmes upon disease activity in CIBD ( • ▶ Table 5). All 11 investigations have reported benefit in terms of reduced disease activity, although in some cases the experimental designs were not very satisfactory.…”
Section: Disease Activitymentioning
confidence: 99%
“…6 studies of varying quality [15,21,34,41,47,48] have all reported an increase in the quality of life in patients with IBD following an increase of habitual physical activity, commonly linked to functional gains.…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Given there are no evidence-based guidelines or recommendations regarding type, duration and intensity of exercise for IBD patients [30], we selected an individualised 'Treat-to-Target' strategy for the exercise advice intervention, aiming to initiate a ≥30% increase in PA levels [31]. The regime for the ω-3 FA intervention was comparable with the dose and frequency of regimes used in studies on the effect of ω-3 FA on IBD disease activity [1,32].…”
Section: Introductionmentioning
confidence: 99%